The Role of E-Commerce in Empowering Cooperatives: Digital Implementation and the Spirit of Collectivism - Made Yudi Darmita; Ida Bagus Raka Suardana; A.A.N Eddy Supriyadinata Gorda; Ida Ayu Oka Martini (Jurnal Ekonomi dan Bisnis Jagaditha, 2026)
This study aims to understand the transformation of digital services and cooperative accountability through internalization of the culture of joy and sorrow in cooperatives. The principle of the family in cooperative management is presented as a manifestation of the local value of Tri Hita Karana in the form of activities that balance harmony. An interpretive qualitative approach inspired by a culture of joy and sorrow was used to understand the experience of digital transformation and cooperative management. Five informants who met the criteria as managers or heads of cooperatives were involved in the in-depth interviews. Research informants are representatives of cooperatives that have digitally transformed and carry a culture of joy and sorrow. The results of the analysis found three main findings. First, digital transformation increases the reach and effectiveness of services along with transparency in reporting cooperative management. Second, the presence of the regional and central governments supports and encourages technological transformation, which is expected to become a facilitator in the future. Third, the culture of joy and sorrow is translated into cooperative activities based on Tri Hita Karana’s philosophical values of maintaining harmony with the Creator, fellow cooperative members, and a sense of concern for the universe. This research is novel in that it internalizes the principle of family in cooperative management, which is the local value of Tri Hita Karana in the form of activities that balance the harmony of members with the Creator, members with cooperative managers, and concern for caring for the universe.